Correlates of Quality of Life and Functional Disability in Body Dysmorphic Disorder. - LeBlanc, Nicole. (Tufts Archival Research Center, 2005)
Objective: Body Dysmorphic Disorder (BDD) is a chronic mental illness characterized by low quality of life and functional disability across multiple domains. Despite the clinical importance of understanding psychosocial impairment in BDD, there has been little research examining the factors that contribute to these outcomes. The present study was designed to examine the socio-demographic and clinical correlates of low quality of life as well as work, social, and family disability in a sample of individuals with BDD symptoms. Method: Participants completed an internet survey designed to gather information on demographics, BDD phenomenology, treatment, and impairment. Participants' surveys were included in the final sample (N=256) only if they had completed all study measures and received a score of ≥16 on the 10-item Yale-Brown Obsessive Compulsive Scale, Modified for BDD (BDD-YBOCS), indicating the presence of clinical BDD symptoms. Quality of life and functional disability were assessed with the Quality of Life Enjoyment and Satisfaction Scale - Short Form (Q-LES-Q SF) and the Sheehan Disability Scale (SDS). Results: BDD symptom severity was negatively associated with quality of life and positively associated with disability in all domains. In addition, being female, having no medical insurance, being older, having more severe depression symptoms, having more severe anxiety symptoms, and having more body-parts concerns were predictive of lower quality of life. Public medical insurance and more severe depression symptoms were predictive of greater work disability while Asian ethnicity, single marital status, and more severe depression symptoms were predictive of greater social disability. Older age, more severe depression symptoms, and more severe anxiety symptoms were predictive of increased family disability. Conclusion: Results suggest the multidimensional nature of quality of life and functional disability. Implications for research and treatment are discussed.